Atomic Structure Evolution of Pt–Co Binary Catalysts: Single Metal Sites versus Intermetallic Nanocrystals. Issue 48 (4th October 2021) - Li, Xing; He, Yanghua; Cheng, Shaobo; Li, Boyang; Zeng, Yachao; Xie, Zhenhua; Meng, Qingping; Ma, Lu; Kisslinger, Kim; Tong, Xiao; Hwang, Sooyeon; Yao, Siyu; et al.
Abstract: Due to their exceptional catalytic properties for the oxygen reduction reaction (ORR) and other crucial electrochemical reactions, PtCo intermetallic nanoparticle (NP) and single atomic (SA) Pt metal site catalysts have received considerable attention. However, their formation mechanisms at the atomic level during high‐temperature annealing processes remain elusive. Here, the thermally driven structure evolution of Pt–Co binary catalyst systems is investigated using advanced in situ electron microscopy, including PtCo intermetallic alloys and single Pt/Co metal sites. The pre‐doping of CoN4 sites in carbon supports and the initial Pt NP sizes play essential roles in forming either Pt3 Co intermetallics or single Pt/Co metal sites. Importantly, the initial Pt NP loadings against the carbon support are critical to whether alloying to L12 ‐ordered Pt3 Co NPs or atomizing to SA Pt sites at high temperatures. High Pt NP loadings (e.g., 20%) tend to lead to the formation of highly ordered Pt3 Co intermetallic NPs with excellent activity and enhanced stability toward the ORR. In contrast, at a relatively low Pt loading (< 6 wt%), the formation of single Pt sites in the form of PtC3 N is thermodynamically favorable, in which a synergy between the PtC3 N and the CoN4 sites could enhance the catalytic activity for the ORR, but showing insufficient stability. Abstract : Key factors determining whether the alloying or atomization of Pt NPs on a single Co site rich carbon support are dynamically revealed, including initial Pt loadings, particle sizes, the nature of the carbon supports, and the annealing conditions. The corresponding ordered Pt3 Co intermetallic and single Pt/Co site (i.e., PtC3 N/CoN4 ) catalysts are evaluated for the oxygen reduction reaction. The established structure–property correlations shed light on the design of advanced Pt‐based electrocatalysts.